Phenomenon polysemyy and leksycheskoy omonymyy byolohycheskoy terminology in Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In Article solved Criteria razhranychenyya polysemyy and leksycheskoy omonymyy in byolohycheskoy terminology. Proved, that mnohoznachnost razvyvayut odnoslovnыe of Terms vtorychnoy nomynatsyy, kotorыe ymeyut more than two values. Omonymyya Biology termynov obuslovleno rubbed semantycheskyh bonds Between lexical variants semantycheskymy polysemycheskoho words.
Keywords: omonymyya; polysemyya; Sam semantycheskyy analysis